2006
DOI: 10.1080/02724980543000088
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of immediate activation of gender information from a social role name

Abstract: Two experiments investigated whether the stereotypical gender of a character is encoded immediately into the discourse representation and influences later comprehension. In Experiment 1 people read, and were confused by, a short story in which an incongruity arises at the end if the gender of a character introduced by a social role name has been inferred. In Experiment 2 online measures confirmed that readers were slower to read the final clause of the passage. In addition, a follow-up verification question re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 23 publications
5
52
1
1
Order By: Relevance
“…As such, the provision of social consensus feedback did not succeed in wholly eradicating the stereotyping effect and adds to previous findings which show that stereotype biases are highly resistant to change (e.g. Oakhill et al, 2005;Reynolds et al, 2006).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…As such, the provision of social consensus feedback did not succeed in wholly eradicating the stereotyping effect and adds to previous findings which show that stereotype biases are highly resistant to change (e.g. Oakhill et al, 2005;Reynolds et al, 2006).…”
Section: Discussionsupporting
confidence: 53%
“…Much evidence currently supports the idea that gender is activated elaboratively once a stereotyped role noun is encountered (e.g. Oakhill et al, 2005;Pyykkönen, Hyönä, & van Gompel, 2010;Reynolds, et al, 2006) and that these gender biases affect language comprehension in a backward manner, while resolving anaphors that refer back to a stereotyped role name (e.g. builder…s/he) e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Formally an antecedent is generic wherever the gender of the antecedent is unknown. However, extensive research has shown that antecedents that have a strong gender stereotype might be formally generic but they are not treated as gender-neutral during online language processing (e.g., Esaulova, Reali, & von Stockhausen, 2013;Garnham, Oakhill, & Reynolds, 2002;Kreiner et al, 2008;Oakhill, Garnham, & Reynolds, 2005;Reynolds, Garnham, & Oakhill, 2006;Sturt, 2003). At an intuitive level it follows that there might be a scale of "generic-ness" based on the realworld likelihood, or probability that an antecedent has a specific gender, with low-expectancy antecedents (a cyclist) being treated as highly generic and high-expectancy antecedents (a mechanic) being treated as somewhat generic.…”
Section: Introductionmentioning
confidence: 99%